The relationship between change and religious movements - Kirsti Suolinna (Scripta Instituti Donneriani Aboensis, 1976)
Change constitutes different things for the groups, as the position of one group may improve, but that of another deteriorate. Social change is a consequence of how the different groups act, and their actions again depend on their social and economic interests. In other words, there are groups in society (social classes, professional groups, the agrarian population, industrial workers), which come more or less openly in conflict with each other when looking after their interests. Thus this way of thinking is based on a conflict model. One sees social change as a consequence of people trying to protect their social and economic interests. Viewed this way even religious organizations and movements are involved in protecting the interests of social groups. However, the interesting point in this connection is that religious movements differ from political movements and groups, as the religious movements express the social interests of a group more indirectly than the political movements. The religious movements gather people from similar living conditions, and so to speak, prepare them for political work. They defend and justify the way of living of a group, and thus give ideological material for political groupings. They may also form coalitions with political groups and parties. The author analyzes Laestadianism from this point of view. Before going into the connection between religious dynamics and social change it is necessary to present a few general features of Laestadianism as a religious movement of the peasant population.